A Pilot Study of Loving-Kindness and Self-Compassion Meditation on Depressive Symptoms among People Living with HIV - Rinaldi, Martaria Rizky; Putrikita, Katrim Alifa; Ismail, Abdul Kholiq (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2026)
Individuals living with HIV frequently experience elevated depressive symptoms due to chronic stress, stigma, and emotional burden. Compassion-based interventions such as Loving-Kindness and Self-Compassion Meditation (LKCM) have the potential to improve emotional well-being, yet evidence in HIV-positive populations remains limited. This study examined the preliminary effects of a brief Loving-Kindness and Self-Compassion Meditation (LKCM) intervention on depressive symptoms among individuals living with HIV. It was hypothesized that participants receiving LKCM would show greater reductions in depression than those in a control condition. Using a quasi-experimental pretest–posttest control group design, 18 participants were assigned to either an experimental group (n = 10) that received a two-session LKCM intervention or a no-treatment control group (n = 8). Depressive symptoms were assessed using the DASS-21 depression subscale before and after the intervention. The results revealed significant reductions in depressive symptoms over time in both groups, with a greater magnitude of reduction in the LKCM group; however, between-group differences did not reach statistical significance. Effect size estimates indicated a pattern of greater within-group change in the LKCM group, without supporting conclusions regarding intervention-specific benefits. These findings provide preliminary evidence that LKCM may offer short-term psychological benefits for individuals living with HIV, although definitive conclusions regarding effectiveness cannot be drawn. Larger, adequately powered trials with extended follow-up are warranted to confirm these findings and clarify the potential role of LKCM as a depression management strategy in resource-limited settings.